Global China beyond grand strategy: Rethinking diaspora youth engagement from the ground up - LIU, Jiaqi (Institutional Knowledge at Singapore Management University, 2025)
Since the 2010s, China has embarked on a bold reconfiguration of its global presence, marked by financial diplomacy, infrastructure projects, cultural outreach, and media expansion. Sociologist Ching Kwan Lee (2018) conceptualizes these assertive, outward-facing strategies of geopolitical ascendence as “Global China.” In particular, under Xi Jinping’s leadership, the Chinese diaspora has been positioned as vital conduits for projecting China’s influence in their host countries (Adamson and Han 2024). Through the frameworks of “grand diaspora governance” and “diaspora public diplomacy,” the Chinese state has emphasized the indispensable role of Chinese emigrants as grassroots intermediaries in fostering goodwill and amplifying China’s soft power abroad (Liu 2022b).